Do E-Service Quality and Customer Satisfaction Affect Loyalty in E-Retailing? Evidence from Ghanaian Online Consumers - Samuel Antwi; Patrick Kweku Gbolonyo; Changbing Jiang (Universitas Airlangga, 2022)
This present research investigates the role of e-service quality and customer satisfaction in loyalty creation among Ghanaian online consumers. 403 sample data were collected from Ghanaian consumers who shop on an online shopping platform. The findings indicate three dimensions of e-service quality; reliability, product selection, and customer service are key determinants of customer satisfaction, in addition to customer satisfaction also being a key determinant of loyalty. Nevertheless, reliability, product selection, customer service, and delivery service had no direct influence on loyalty. The mediation role of customer satisfaction, the study implications, as well as limitations are all presented.